Progress of Nigerian National Open Science Roadmap and Infrastructure Development - Iyoha, Owen (My University, 2023)
This presentation was delivered at Open Repositories 2023 Conference as part of Panel 7: LIBSENSE Africa - Breaking down silos across infrastructures to improve the visibility of African research outputs.
Keywords: Infrastructure Development; OPen Science; National Roadmap